A Snapshot of Violence and Criminalization Against Journalists in Indonesia: Enhancing the Safety of Journalists - Marcella Elwina Simandjuntak; Petrus Soerjowinoto; Emilia Metta Karunia Wijaya; Hana Mumtazah (Universitas Negeri Semarang, 2024)
The press and freedom of speech play crucial roles in advancing democracy, fostering good governance, and promoting human development globally. However, despite their critical importance, journalists in Indonesia and other nations face escalating violence. This violence encompasses physical, psychological, and even sexual harm, compounded by the legal repercussions imposed by certain laws that potentially criminalize journalistic activities. This paper aims to explore incidents of violence against journalists and analyze specific provisions within Indonesia's existing Penal Code, the Information and Electronic Transactions Act (UU ITE), and the Personal Data Protection Act that could be utilized to criminalize journalists. The application of these laws poses significant threats to press freedom, media impartiality, and the integrity of information dissemination. Using a normative legal approach, this study draws on data derived from existing laws, online resources, research studies, and contemporary literature. Employing a descriptive-qualitative analysis, the findings underscore the prevalence of violence against journalists across Indonesia, with frequent violations of their rights to access information through intimidation, harassment, and various forms of physical and psychological coercion. Furthermore, journalists face potential imprisonment under the provisions of Indonesian laws, exacerbating the climate of fear among media professionals. The implications of these threats include a chilling effect on media freedom, hindering the free flow of information, diverse opinions, and critical ideas essential for an informed citizenry. Addressing these challenges requires robust protections for journalists, stringent adherence to international standards of press freedom, and reforms to ensure that laws safeguard rather than restrict journalistic activities.